2005
DOI: 10.1007/s15010-005-4040-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection among Low-Risk First Lifetime Testers in Rome, 1990?2000

Abstract: Our findings are consistent with data from other industrialized countries and they show a strong association between HIV seropositivity and reason for first-time testing. Moreover, they indicate a stable trend of HIV prevalence among low-risk persons in the last decade. Further studies on time trends in low-risk populations would be useful to evaluate current HIV prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Prevalence among this group was 1.2% (95% CI 0.6–2.0%) compared with 0.4% (95% CI 0.3–0.5%) in other clients of the same site. 8…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence among this group was 1.2% (95% CI 0.6–2.0%) compared with 0.4% (95% CI 0.3–0.5%) in other clients of the same site. 8…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence among this group was 1.2% (95% CI 0.6-2.0%) compared with 0.4% (95% CI 0.3 -0.5%) in other clients of the same site. 8 Among the papers presenting HIV prevalence according to time periods, eight papers presented time trends among all clients for three or more consecutive years. Seven of the eight papers showed a decline in HIV prevalence.…”
Section: Concentrated Epidemicsmentioning
confidence: 99%
“…Six of them, all from the U.S., predated the introduction of highly active ART in 1996, 31,48e52 and five were conducted in the era of ART. 22,25,32,53,54 Pain (11 Studies) Table 2 displays the findings in the domains of pain and physical problems, by population group. In prospective observational studies, pain prevalence ranged from 31% to 53% in middle-income country outpatient populations, 46,55 and was 76% among low-income country patients with AIDS 41 and 69% for inpatients with herpes zoster.…”
Section: Populations and Settingsmentioning
confidence: 99%
“…In Italy, 7% of people with HIV from ''low-risk'' groups reported testing because of ''alarming symptoms.'' 54 Forty-three percent of recent seroconverters in Canada took an HIV test because of symptoms or illness, 29 compared with 33% of the HIV-positive population in Tanzania. 42 In the U.K., patient's records showed that 37% of black Africans and 19% of whites tested HIV positive after symptoms.…”
Section: Physical (22 Studies)mentioning
confidence: 99%